Hemophagocytic Lymphohistiocytosis in a Patient With Hodgkin lymphoma and Concurrent EBV, CMV, and Infections - Moaath Mustafa Ali MD; Ana Lucia Ruano Mendez MD; Hetty E. Carraway MD, MBA, FACP (SAGE Publishing, 2017)
Hemophagocytic lymphohistiocytosis (HLH) is a syndrome characterized by immune activation and subsequent widespread organ damage. Patients affected by HLH commonly develop fever, cytopenias, liver damage, neurologic manifestations, and hypercytokinemia. In this case, we describe a 60-year-old male who presented with HLH and concurrent Epstein-Barr virus, cytomegalovirus, and Candida infections and was subsequently diagnosed with a Hodgkin lymphoma. This case highlights the importance of considering a cancer diagnosis in the differential diagnosis of patients presenting with HLH.